2013
DOI: 10.1002/ajhb.22389
|View full text |Cite
|
Sign up to set email alerts
|

Decreased external skeletal robustness due to reduced physical activity?

Abstract: We demonstrate an association between external skeletal robustness and physical activity, which is not captured by in BMI measurements. Children should be physically active in order to maintain skeletal robustness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 38 publications
7
55
0
2
Order By: Relevance
“…Reduced physical activity is not only one of the reasons for obesity but also affects external skeletal robustness which is decreased [14], [15]. A ten year comparison showed that new trend in German 6–12 years-olds boys and girls [16].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced physical activity is not only one of the reasons for obesity but also affects external skeletal robustness which is decreased [14], [15]. A ten year comparison showed that new trend in German 6–12 years-olds boys and girls [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is very little published information to rely on, Rietsch et al (2013) documented an association between physical activity and relative elbow breadth in children that seems disconnected from factors that promote the secular increase in height. Bigec (2013) also report on a positive secular change in height and lower limb length that is in the reverse direction of elbow and knee breadth, which show a negative trend, although inconsistently.…”
Section: Discussionmentioning
confidence: 99%
“…If secular changes in height are taken to represent changes in long bone length then there is considerable evidence for an increase in size for most, if not all, populations of developed nations and several developing nations (Hauspie et al, 1997). This is a clear indication of the Although there is very little published information to rely on, Rietsch et al (2013) documented an association between physical activity and relative elbow breadth in children that seems disconnected from factors that promote the secular increase in height. Bigec (2013) In part, these inconsistencies may occur because the dimensions of the knee joint are likely to reflect changes in body weight, due to its load bearing function.…”
Section: Discussionmentioning
confidence: 99%
“…German children followed over a 10‐year period were found to have decreasing Frame‐Index values (Scheffler, ). Rietsch, Eccard, and Scheffler () compared German and Russian children over a course of 10 years and found that children of both nationalities showed decreasing Frame‐Index values, although the Russian children had higher values than the German children Rietsch, Godina, & Scheffler, . It has also been reported that the Frame‐Index in children has a positive relationship with not only BMI but also BF% and stronger with physical activity (PA) (Rietsch, Eccard, & Scheffler, ).…”
Section: Introductionmentioning
confidence: 99%